HUBUNGAN KEHARMONISAN KELUARGA DENGAN DISIPLIN PESERTA DIDIK TAMAN PENDIDIKAN AL-QURAN BAITUL HASANAH KECAMATAN SUMPUR KUDUS KABUPATEN SIJUNJUNG - Eby Anggraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2015)
This research is conducted based on the low condition of the student’s discipline in Al-Qur’an Education Center Baitul Hasanah. It is presumed because of less the student to the family harmonism. This research is aimed to observe how is the image of perception to family harmonism, condition of the students’ discipline in Al-Qur’an Education Center Baitul Hasanah, and also to see the relationship between to the family harmonism and the student’s discipline in the Al-Qur’an Education Center Baitul Hasanah. This research is co relational- quantiative research which the subject of this research is taken from the student of Al-Qur’an Education Center Baitul Hasanah. The number of the subject is 20 students. The result of the research is showed that there is a significant relationship between the family harmonism and student’s discipline in Al-Qur’an Education Center Baitul Hasanah.